RESPON PERTUMBUHAN DAN HASIL KACANG PANJANG VARIETAS LOKAL PADA BERBAGAI DOSIS PUPUK ORGANIK - Josina Irene Brigetha Hutubessy; Engelbertus Doni Welan; Kristono Yohanes Fowo (AGRICA, 2022)
Growth Response And Production Of Local Variety Of Long Bean At Various Dosages Of Organic Fertilizer. Red long bean is one of the leguminous plants that has a high nutritional content and plays an important role in meeting the nutritional needs of the whole community and has great opportunities, but the productivity of long beans produced is still very low, the use of manure is expected to increase productivity and quality. from a healthy growing environment. The aim of the study was to determine the effect of organic pig manure and to obtain the optimum dose on the growth and yield of red long bean. The study used a randomized block design (RAK) consisting of 5 doses of organic pig manure, namely: P0 = no fertilizer, P1 = 7.5 tons/ha-1 or 2.7 kg/plot, P2 = 15 tons/ha -1 or 5.4 kg/plot, P3 = 22.5 tons/ha-1 or 8.1 kg/plot, P4 = 30 tons/ha-1 or 10.8 kg/plot. The variables observed were number of leaves (strands), leaf area (cm2), number of pods per plant (fruit), pod weight per plant (gr), pod weight per Ha (tons/ha). The results showed that the application of organic fertilizer from pig manure had a very significant effect on the variables of leaf number, leaf area, number of pods, weight of planted pods and weight of pods per hectare with an increase in each observation variable of 11.82% for the number of leaves; leaf area by 20.07%; the number of pods by 21.47%; the weight of the pods planted was 29.24% and the weight of the pods per hectare was 29.21%.